PENGETAHUAN GURU PUSAT KEGIATAN BELAJAR MASYARAKAT X MENGENAI PESERTA DIDIK BERKEBUTUHAN KHUSUS - Yunita, Intan; Purwanti, Margaretha (MANASA, 2025)
The Community Learning Activity Centre (Pusat Kegiatan Belajar Masyarakat/PKBM) is a non-formal educational institution that provides a 12-year basic education equivalent. PKBM X in Jakarta has students with special educational needs. As an inclusive PKBM, teachers are expected to have knowledge about students with special educational needs (PDBK). Learning at PKBM X is reportedly suboptimal due to a lack of teacher knowledge about PDBK. Therefore, it is important to assess the basic knowledge that PKBM X teachers have about PDBK. The teacher knowledge measured in this study is based on knowledge and basic-level cognitive processes in Bloom's Taxonomy. This descriptive quantitative study involved 58 teachers from ten PKBM X branches in Indonesia. The measuring instrument is a questionnaire about teachers' knowledge. The results showed that 55.17% of teachers had insufficient knowledge, 31.03% had sufficient knowledge and just 13.79% had a good grasp of the subject. This insufficient knowledge was mainly related to strategies for handling PDBK, with an average score of 48.85%. The same applies to the application domain in Bloom's Taxonomy, where the average knowledge is 51.47%. It is suspected that the PKBM X teachers' lack of knowledge stems from inadequate training in PDBK.